Perinatal predictors of parenting stress trajectories during the first 3 years of parenthood: A Maternal and Child Health Handbook cohort study - Nao Oikawa; Mariko Hosozawa; Syudo Yamasaki; Shuntaro Ando; Mitsuhiro Miyashita; Kaori Baba; Junko Niimura; Naomi Nakajima; Satoshi Yamaguchi; Yuko Morimoto; Sho Kanata; Hiroyasu Iso; et al. (JCPP Advances, 2026)
Abstract Background Evidence of how parenting stress evolves during early childhood is limited. We aimed to identify parenting stress trajectories involving children aged 1 month to 3 years, and to determine their perinatal predictors. Methods Data were obtained from 3133 mothers in the Tokyo Teen Cohort (TTC), a population‐based cohort of children born between 2002 and 2004. Parenting stress was self‐recorded in the Maternal and Child Health Handbook (MCHH) at eight time points between 1 and 36 months postpartum. Latent class growth analysis identified trajectories; multivariate multinomial logistic regression analyzed baseline predictors from the MCHH or the TTC first wave. Results Five distinct trajectories were identified: consistently low ( n = 1,691, 54.0%), consistently high ( n = 158, 5.0%), consistently moderately high ( n = 719, 22.9%), high‐decreasing ( n = 299, 9.5%), and low‐increasing ( n = 266, 8.5%). Compared with the consistently low group, primiparity predicted all trajectories with initially high stress: consistently high (adjusted odds ratio [aOR] 1.64, 95% confidence interval [CI] 1.13–2.37), consistently moderately high (aOR 1.92, 95% CI 1.57–2.35), and high‐decreasing (aOR 1.87, 95% CI 1.38–2.54). Preterm birth also predicted the consistently high trajectory (aOR 2.38, 95% CI 1.31–4.32). Maternal alcohol consumption during pregnancy (aOR 1.33, 95% CI 1.06–1.67) and male sex (aOR 0.80, 95% CI 0.66–0.97) predicted the consistently moderately high trajectory. High maternal education (aOR 1.58, 95% CI 0.99–2.52) tended to predict the low‐increasing trajectory. Maternal age, chronic health conditions, smoking during pregnancy, single‐parent household, and history of infertility treatment were not significant predictors. Conclusion Parenting stress follows heterogenous trajectories, necessitating repeated assessments during the first 3 years. Integrating systematic, self‐recorded screenings into routine check‐ups could facilitate the timely identification of evolving stress patterns. Recognizing early predictors, including primiparity and preterm birth, can further assist in identifying mothers warranting closer longitudinal monitoring.